Nursing care for patients with Acute Respiratory Distress Syndrome (ARDS) in the intensive care unit at dr. Zainoel Abidin General Hospital - Elsa Fitria; Jufrizal Jufrizal (PT WIM Solusi Prima, 2026)
Acute Respiratory Distress Syndrome (ARDS) is a condition of acute respiratory failure characterized by increased permeability of the alveolar-capillary membrane and pulmonary edema, leading to impaired gas exchange and severe hypoxemia. ARDS can occur in critically ill patients due to various conditions, including complications following major surgery. This condition often requires mechanical ventilation support and intensive monitoring in the Intensive Care Unit (ICU). The purpose of this case study was to describe nursing care for patients with ARDS in the Intensive Care Unit at dr. Zainoel Abidin Regional General Hospital. The methodology used was a case study employing the nursing process, including assessment, diagnosis, planning, implementation, and evaluation. Assessment findings indicated several nursing diagnoses, such as impaired gas exchange, hypovolemia, risk of aspiration, risk of infection, and ineffective renal tissue perfusion. Nursing interventions focused on mechanical ventilation management, monitoring of respiratory and hemodynamic status, fluid and organ perfusion stabilization, prevention of aspiration, and prevention of infections resulting from the use of invasive devices during care in the ICU. The conclusions of this case study indicate that the patient experienced progressive clinical deterioration, including unstable gas exchange, persistent hypotension, acute kidney failure, and the development of shock with multiple organ failure despite receiving optimal therapy. It is hoped that the management of patients with ARDS following major surgery can be carried out promptly, comprehensively, and collaboratively to prevent more severe complications.